The effect of aging time on mechanical and microstructure properties of aa6061 joints welded by gas tungsten arc welding - Ahmad, R (Juniper Publisher, 2018)
This research examines the influence of heat treatment on mechanical properties and microstructure of AA6061 aluminium alloy welded with butt groove method, by using Gas Tungsten Arc Welding (GTAW) method. Welded samples were divided into two; heat treated (PWHT) and as-welded (AW) joints samples. For PWHT welded samples, the heat treatment applied were solution heat treatment at a temperature of 5300C for 1 h, followed by cooling water and artificial aging process at a temperature of 1600C for 18, 20 and 22 hours. Tensile test was performed based on standard ASTM E8 04, while the hardness test was taken at 3 different locations along the cross section of the weld zone of upper, middle and lower sections. Fracture surface at AW and PWHT welded samples were investigated by using Scanning Electron Microscopy (SEM) and the microstructure of the samples was analyzed by using Optical Microscopy (OM). From the results, the PWHT welded samples increased the tensile strength, hardness, and micro structural characteristics of welded joints aluminium AA6061 alloy.